Atomic density at high-angle grain boundaries in tungsten - Ksenofontov, V.A.; Mazilov, A.A.; Mazilova, T.I.; Sadanov, E.V.; Sokolenko, V.I.; Voyevodin, V.N.; Dudka, O.V.; Mikhailovskij, I.M. (Вопросы атомной науки и техники, 2011)
The oscillatory features of the atomic relaxation and the phenomenon of plane coalescence on high-angle grain boundaries in tungsten are studied by the methods of molecular statics and field ion microscopy. A nonmonotonic character of the variation of the atomic density in the near-boundary region is established. The strain field normal to the boundary plane is calculated and compared with the results obtained using the embedded-atom method in the reciprocal space. It is shown that the amplitude, period, and character of damping of the oscillations near grain boundaries can be described satisfactorily in the framework of the line forces model. Методами молекулярної статики і польової іонної мікроскопії вивчені явища коалесценції атомних площин і характер атомної релаксації, який осцилює на великокутових межах зерен у вольфрамі. Встановлено немонотонний характер зміни атомної густини в примежовій області. Розраховані поля напруг, які нормальні площини межі, і проведено порівняння з результатами, отриманими з використанням методу зануреного атома в зворотному просторі. Показано, що амплітуда, період і характер загасання осциляцій поблизу межі можуть бути задовільно описані за допомогою моделі лінійних сил. Методами молекулярной статики и полевой ионной микроскопии изучены явление коалесценции атомных плоскостей и осциллирующий характер атомной релаксации на большеугловых границах зерен в вольфраме. Установлен немонотонный характер изменения атомной плотности в приграничной области. Рассчитаны поля напряжений, нормальные плоскости границы, и проведено сравнение с результатами, полученными с использованием метода погруженного атома в обратном пространстве. Показано, что амплитуда, период и характер затухания осцилляций вблизи границы могут быть удовлетворительно описаны в рамках модели линейных сил.